Evolutionary patterns of the mitochondrial control region in vertebrates: A large-scale comparative analysis - Mauricio Ochoa Capera; Natalia S. Medina; Paula Montaña-Lozano; Manuela Moreno-Carmona; Antonio Baeza; Carlos Prada-Quiroga (PLoS ONE, 2026)
The mitochondrial control region (CR) is the largest non-coding region in the vertebrate mitogenome and contains essential elements for replication and transcription. Despite its functional relevance, its evolutionary dynamics remain poorly understood. Here, we analyzed 5,235 complete vertebrate CRs spanning 11 classes to investigate how conserved sequences blocks (CSBs) and Extended Termination-Associated sequences (ETAS) shaped CR evolution. We hypothesized that CR length is positively associated with repeat accumulation, with tetrapods exhibiting longer and more complex CRs than fishes, while core elements remain conserved. Our analyses revealed marked inter- and intra-class variability, with longer CRs in tetrapods (1,283.27 ± 489.6 bp) than in fishes (969.25 ± 239.5 bp). Duplication events were restricted to tetrapods, especially birds and reptiles. Nucleotide composition was heterogeneous among orders, and structural divergence of CSBs was inferred across lineages. Repetitive elements were present in ~43% of CRs, with their abundance strongly correlated with CR length. Importantly, longer CRs were associated with higher GC content and greater variation in copy number of ETAS and CSBs. These results demonstrate that mitogenome CR expansion in vertebrates is largely driven by repeat proliferation, whereas key motifs required for replication and transcription are retained. We further identify lineage-specific trends, including pronounced CR elongation in amphibians and reptiles, contrasted with progressive reduction and simplification in birds and mammals. Our study provides the first comprehensive comparative framework of vertebrate CR evolution, highlighting how repetitive elements, conserved motifs, and nucleotide composition jointly contribute to both functional regulation and lineage-specific diversification.